2009
DOI: 10.1509/jppm.28.2.212
|View full text |Cite
|
Sign up to set email alerts
|

Betrayed by the Buzz? Covert Content and Consumer–Brand Relationships

Abstract: Brands are increasingly sponsoring online communications that do not identify their commercial source as a way to break through advertising clutter and to circumvent consumer cynicism toward traditional advertising. The results of lab studies indicate that these covert actions decrease trust in and commitment to brand users and that this effect is strongest when the brand user's emotional connection to the brand is threatened. Thus, use of covert marketing campaigns to overcome challenges with advertising may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
55
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(59 citation statements)
references
References 45 publications
(58 reference statements)
1
55
0
3
Order By: Relevance
“…Trust acts like a bridge between satisfaction and individual relationships and directs positive transaction towards close relationships between brands and individuals (Hess & Story, 2005). Trust reflects certainty, honesty and ability in relationship between a brand and a consumer which is attributed to a brand by consumers (Ashley & Leonard, 2009). Trust in brand has two dimensions: 1.…”
Section: Trust In Brandmentioning
confidence: 99%
“…Trust acts like a bridge between satisfaction and individual relationships and directs positive transaction towards close relationships between brands and individuals (Hess & Story, 2005). Trust reflects certainty, honesty and ability in relationship between a brand and a consumer which is attributed to a brand by consumers (Ashley & Leonard, 2009). Trust in brand has two dimensions: 1.…”
Section: Trust In Brandmentioning
confidence: 99%
“…Renewable electricity, however, has a higher differentiation factor and is considered a high involvement product (Claudy, Michelsen and O'Driscoll, 2011) since consumers can have personal values connected to green electricity and an increased engagement to the product as a brand (Ashley and Leonard, 2009). In this research, however, the participants showed very limited engagement with green energy, not least to the impacting factors identified.…”
Section: Impacting Constructmentioning
confidence: 63%
“…Bird, Holt and Carroll, 2008) but consumer perceptions of what comprises a renewable source are not clear (Bergmann, Hanley and Wright, 2006;Borchers, Duke and Parsons, 2007;Ashley and Leonard, 2009;Larsen, 2013). The term "green electricity" commonly refers to electricity produced by technologies that do not vent damaging emissions into the atmosphere (Paladino and Pandit, 2012) and are generated from environmentally preferable energy sources (Truffer, Markard and Wüstenhagen, 2001).…”
Section: Defining Green Electricitymentioning
confidence: 99%
“…Several recent studies have examined covert practices in the contexts of website sponsorship (Ashley and Leonard 2009), Internet cookie use (Miyazaki 2008), and online communities (Milne et al 2009). The findings suggest that when covert persuasion practices are uncovered, the mere knowledge of hidden intervention can lead to negative consumer attitudes toward marketers.…”
Section: Journal Of Marketing Communications 225mentioning
confidence: 99%
“…The escalating controversy surrounding covert marketing is made apparent by an increasing number of scholarly studies (e.g., Martin and Smith 2008;Rotfeld 2008) and regulatory interventions (FTC 2005(FTC , 2006(FTC , 2008(FTC , 2009. Prior studies have documented that consumers have less favorable brand attitudes and lower purchase intentions when they realize that a product is marketed covertly (Wei, Fischer, and Main 2008;Ashley and Leonard 2009;Milne, Rohm, and Bahl 2009). Interestingly, research also indicates that covert marketing may provide useful information in an unobtrusive manner, and helps to minimize consumers' cognitive dissonance (Milne et al 2008).…”
mentioning
confidence: 99%